1998
DOI: 10.1177/030089169808400310
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic Changes; Plasma Levels of Alpha2-Antiplasmin-Plasmin Complex and Thrombin-Antithrombin III Complex in Female Breast Cancer

Abstract: We demonstrated that increased APP and TAT levels might reflect enhanced activation of coagulation and the fibrinolytic system in patients with active breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Because the cAT content in the plasma declined after tumor excision surgery and was generally associated with PADI4 levels in the blood, we propose that the high cAT levels observed in the blood was due to citrullination of PADI4 in tumor tissues. Suppressed antithrombin III activity and unregulated thrombin activity have broadly been reported in the plasma of patients with lung adenocarcinomas, renal cell carcinomas, breast cancer, malignant melanomas, colon cancer, pancreatic adenocarcinomas, and larynx squamous cell carcinomas [13-16]. Thrombin activity can promote angiogenesis by increasing transcription of the VEGF receptor as well as metastasis and hyperplasia by inducing expression of integrin β 3 [17-19].…”
Section: Discussionmentioning
confidence: 99%
“…Because the cAT content in the plasma declined after tumor excision surgery and was generally associated with PADI4 levels in the blood, we propose that the high cAT levels observed in the blood was due to citrullination of PADI4 in tumor tissues. Suppressed antithrombin III activity and unregulated thrombin activity have broadly been reported in the plasma of patients with lung adenocarcinomas, renal cell carcinomas, breast cancer, malignant melanomas, colon cancer, pancreatic adenocarcinomas, and larynx squamous cell carcinomas [13-16]. Thrombin activity can promote angiogenesis by increasing transcription of the VEGF receptor as well as metastasis and hyperplasia by inducing expression of integrin β 3 [17-19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated a hypercoagulable state in breast cancer patients, with elevated markers of coagulation, including thrombin -antithrombin (TAT) (Falanga et al, 1998;Ozyilkan et al, 1998), fibrinogen (Miller and Heilmann, 1988), D-dimer (Blackwell et al, 2000;Oberhoff et al, 2000) and tissue factor (TF) (Lwaleed et al, 1999;Ueno et al, 2000).…”
mentioning
confidence: 99%
“…Increased TAT levels show coagulation activation [22]. Ozyilkan et al determined a similar escalation in patients with breast cancer [23]. Seitz et al observed increased TAT levels in patients with lung cancer [10].…”
Section: Discussionmentioning
confidence: 99%